Prevalence and treatment of opioid use disorders among primary care patients in six health systems. (1st February 2020) - ,; Ahmedani, Brian; Amoroso, Paul J.; Arnsten, Julia H.; Bart, Gavin; Braciszewski, Jordan M.; Cunningham, Chinazo O.; Hechter, Rulin C.; Horigian, Viviana E.; Liebschutz, Jane M.; Loree, Amy M.; Matson, Theresa E.; et al.
Highlights: The OUD prevalence among primary care patients in 6 health systems was 1.0 %. For patients with OUD, the prevalence of treatment with buprenorphine was 21.0 %. Patients with poorest health and greatest acute care use had the lowest treatment. System changes are needed to increase treatment of OUD in primary care patients. Abstract: Background: The U.S. experienced nearly 48, 000 opioid overdose deaths in 2017. Treatment of opioid use disorder (OUD) with buprenorphine is a recommended part of primary care, yet little is known about current U.S. practices in this setting. This observational study reports the prevalence of documented OUD and OUD treatment with buprenorphine among primary care patients in six large health systems. Methods: Adults with ≥2 primary care visits during a three-year period (10/1/2013-9/30/2016) in six health systems were included. Data were obtained from electronic health record and claims data, with measures, assessed over the three-year period, including indicators for documented OUD from ICD 9 and 10 codes and OUD treatment with buprenorphine. The prevalence of OUD treatment was adjusted for age, gender, race/ethnicity, and health system. Results: Among 1, 368, 604 primary care patients, 13, 942 (1.0 %) had documented OUD, and among these, 21.0 % had OUD treatment with buprenorphine. For those with documented OUD, the adjusted prevalence of OUD treatment with buprenorphine varied across demographic and clinical subgroups. OUD treatment was lower among patients who were older, women, Black/African American and Hispanic (compared to white), non-commercially insured, and those with non-cancer pain, mental health disorders, greater comorbidity, and more opioid prescriptions, emergency department visits or hospitalizations. Conclusions: Among primary care patients in six health systems, one in five with an OUD were treated with buprenorphine, with disparities across demographic and clinical characteristics. Less buprenorphine treatment among those with greater acute care utilization highlights an opportunity for systems-level changes to increase OUD treatment.